Neurological disease may precede lymphadenopathies in Actinomyces europaeus infection. Issue 4 (July 2018) - Corcione, Silvia; Curtoni, Antonio; Paolucci, Ivana A.; Di Perri, Giovanni; De Rosa, Francesco G.; Cavallo, Rossana
Abstract: Actinomyces species are part of the commensal flora of the mucous membranes of the oropharynx, gastrointestinal tract and female genital tract. Actinomyces europaeus is a short, nonmotile, facultative anaerobic rod first described in 1997, susceptible in vitro to a wide range of b-lactam antibiotics which are regarded as first choice. In this report we described the case of A. europaeus infection in a young female patient admitted to Intensive Care Unit and the possible damage of vascular endothelium due to a chronic progressive actinomycosis that at first involved neck soft tissue, then cervical lymphnodes, and finally extended to the vascular structure.